The Supervision of Madrasah Principals in Improving Learning Quality Post-Covid-19 Pandemic at Madrasah Aliyah Negeri 1 Merangin - Sobran Sobran; Fridiyanto Fridiyanto; Rusmini Rusmini (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyze the supervision practices of the principal at Madrasah Aliyah Negeri 1 Merangin in improving learning quality post-COVID-19 pandemic. The research explores how the principal implements supervision, the condition of learning quality after the pandemic, and the impact of these supervisory practices on educational outcomes.Using a qualitative research approach, data were collected through observations, interviews, documentation, and triangulation methods. The findings reveal three key aspects: (1) the principal effectively conducts supervision activities, including planning, organizing, motivating, monitoring, and evaluating, through the Learning Supervision Instrument Item Analysis (ABIS) strategy; (2) teachers have systematically structured learning processes, encompassing the development of learning objectives, material selection, teaching strategies, and resource organization, which have positively impacted educational outcomes; and (3) the supervision program implemented by the principal aligns with the overall goal of improving learning quality, resulting in notable progress in post-pandemic educational practices. This research underscores the significant role of effective supervision in enhancing learning quality, particularly in the context of Islamic educational institutions adapting to post-pandemic challenges. The results offer valuable insights for educational leaders and policymakers seeking to develop robust supervisory frameworks to foster continuous improvement in learning outcomes.